Standing on the shoulders of giants: a scholarly leave-taking - Monk, Craig; Patterson, Cynthia Lee; Karen Roggenkamp (My University, 2015)
The academic image of "standing on the shoulders," traced through Sir Isaac Newton in 1676, back to Bernard of Chartres in the twelfth century, compares the production of truth to dwarfs sitting on the shoulders of giants. In this metaphor, the dwarfs rely on their added height to broaden their horizons and expand the scope of known truths. However, the major thrust seemed to be the reliance of these dwarfs on the truths gleaned by their giant predecessors. Now, the editorial triumvirate at American Periodicals do not consider themselves to be scholarly dwarfs, nor their predecessors monstrous giants. Nonetheless, in this editorial address, which coincidentally celebrates the twenty-fifth anniversary of the journal, we do wish to acknowledge the foundation upon which we built our own contributions to the journal as we enter the final year of our editorship. What better way than to feature the remembrances of a headline cast of former AP editors and contributors? Furthermore, from the added height of our past five years' experience editing the journal and the work we have done to secure cutting-edge contributions for future issues, we would like to announce exciting special issues on the horizon. We will close our editorial address by prognosticating some of the challenges we see in the future of scholarly publishing in American periodicals.